Question and Answers Forum

All Questions      Topic List

Algebra Questions

Previous in All Question      Next in All Question      

Previous in Algebra      Next in Algebra      

Question Number 207747 by MASANJAJJ last updated on 25/May/24

find the value of y given that y^(y ) =3^(y+9)

$${find}\:{the}\:{value}\:{of}\:{y}\:{given}\:{that}\:{y}^{{y}\:} =\mathrm{3}^{{y}+\mathrm{9}} \\ $$

Answered by mr W last updated on 25/May/24

y^y =3^y ×3^9   ((y/3))^y =3^9   ((y/3))^(y/3) =3^3   ⇒(y/3)=3 ⇒y=9

$${y}^{{y}} =\mathrm{3}^{{y}} ×\mathrm{3}^{\mathrm{9}} \\ $$$$\left(\frac{{y}}{\mathrm{3}}\right)^{{y}} =\mathrm{3}^{\mathrm{9}} \\ $$$$\left(\frac{{y}}{\mathrm{3}}\right)^{\frac{{y}}{\mathrm{3}}} =\mathrm{3}^{\mathrm{3}} \\ $$$$\Rightarrow\frac{{y}}{\mathrm{3}}=\mathrm{3}\:\Rightarrow{y}=\mathrm{9} \\ $$

Answered by Berbere last updated on 25/May/24

y^y =3^a ⇒a=((yln(y))/(ln(3)))  ⇔3^((yln(y))/(ln(3))) =3^(y+9)   ⇒yln(y)=yln(3)+9ln(3)  yln((y/3))=9ln(3)>0⇒y≥3  y→^f yln((y/3)) increase function over [3,∞[  f′=ln((y/3))+(y/3)≥ln((3/3))+(3/3)=1  f(9)=9ln(3)⇒y=9

$${y}^{{y}} =\mathrm{3}^{{a}} \Rightarrow{a}=\frac{{yln}\left({y}\right)}{{ln}\left(\mathrm{3}\right)} \\ $$$$\Leftrightarrow\mathrm{3}^{\frac{{yln}\left({y}\right)}{{ln}\left(\mathrm{3}\right)}} =\mathrm{3}^{{y}+\mathrm{9}} \\ $$$$\Rightarrow{yln}\left({y}\right)={yln}\left(\mathrm{3}\right)+\mathrm{9}{ln}\left(\mathrm{3}\right) \\ $$$${yln}\left(\frac{{y}}{\mathrm{3}}\right)=\mathrm{9}{ln}\left(\mathrm{3}\right)>\mathrm{0}\Rightarrow{y}\geqslant\mathrm{3} \\ $$$${y}\overset{{f}} {\rightarrow}{yln}\left(\frac{{y}}{\mathrm{3}}\right)\:{increase}\:{function}\:{over}\:\left[\mathrm{3},\infty\left[\right.\right. \\ $$$${f}'={ln}\left(\frac{{y}}{\mathrm{3}}\right)+\frac{{y}}{\mathrm{3}}\geqslant{ln}\left(\frac{\mathrm{3}}{\mathrm{3}}\right)+\frac{\mathrm{3}}{\mathrm{3}}=\mathrm{1} \\ $$$${f}\left(\mathrm{9}\right)=\mathrm{9}{ln}\left(\mathrm{3}\right)\Rightarrow{y}=\mathrm{9} \\ $$$$ \\ $$

Answered by Berbere last updated on 25/May/24

if y∈N^∗   ⇒y=3^a ;a≥1  3^(ay) =3^(y+9)   ay=y+9  y∣ay ⇔y∣y+9⇒y∣(ay−y)=9⇒y∣9  ⇒y∈{1,3,9}⇒y=9 by tcheking

$${if}\:{y}\in\mathbb{N}^{\ast} \\ $$$$\Rightarrow{y}=\mathrm{3}^{{a}} ;{a}\geqslant\mathrm{1} \\ $$$$\mathrm{3}^{{ay}} =\mathrm{3}^{{y}+\mathrm{9}} \\ $$$${ay}={y}+\mathrm{9} \\ $$$${y}\mid{ay}\:\Leftrightarrow{y}\mid{y}+\mathrm{9}\Rightarrow{y}\mid\left({ay}−{y}\right)=\mathrm{9}\Rightarrow{y}\mid\mathrm{9} \\ $$$$\Rightarrow{y}\in\left\{\mathrm{1},\mathrm{3},\mathrm{9}\right\}\Rightarrow{y}=\mathrm{9}\:{by}\:{tcheking} \\ $$$$ \\ $$$$ \\ $$$$ \\ $$

Terms of Service

Privacy Policy

Contact: info@tinkutara.com